Environmental degradation and its effects on the poverty status of broiler farmers in Calabar metropolis, Cross River State, Nigeria - Effiong, M. O; Okere, R.A; Itam, K. O.; Osuafor, O.O. (ADAN JOURNAL OF AGRICULTURE, 2025)
The economic growth process in Nigeria has proven to be environmentally unsustainable and socially inequitable. The effects of poverty, population growth, and degradation are interactive; hence, there is a need to determine the poverty status of broiler farmers and their effects on environmental degradation in Calabar Metropolis in Cross River State. The specific objectives were: To assess the socio-economic characteristics of the broiler farmers, estimate the poverty status of these farmers in the area, assess the effect of environmental degradation on the poor farmers, and estimate the determinants of poverty among the broiler farmers in the area. Descriptive statistics and logistic regression model were used to evaluate the extent of the impact of variables such as sex, marital status, education, farming experience, number of birds, access to improved breeds, and ownership of assets of broiler farmers in Calabar South and Calabar Municipality of Cross River State. Structured questionnaires were administered to 47 heads of households of broiler farmers to generate primary data. Based on the results, three logit coefficients were significant at the 10% significance level in predicting whether a broiler farmer was poor or non-poor, and four other variables were significant at the 5% level. The estimated adjusted R2 value of 0.794 indicates that the strength of association between the independent and the dependent variables is about 79.4%. Also, water/air pollution and solid waste management were positive and significantly related to environmental degradation in the area. The study suggests that improving the broiler farmers' socioeconomic status would enhance their productivity and increase profitability, thus reducing the poverty rate among them.